From frontier policy to foreign policy : the question of India and the transformation of geopolitics in Qing China - Mosca, Matthew W. (Stanford University Press, 2013)
Between the mid-eighteenth and mid-nineteenth centuries, Qing rulers, officials, and scholars fused diverse, fragmented perceptions of foreign territory into one integrated worldview. In the same period, a single 'foreign' policy emerged as an alternative to the many localized 'frontier' policies hitherto pursued on the coast, in Xinjiang, and in Tibet. By unravelling Chinese, Manchu, and British sources to reveal the information networks used by the Qing empire to gather intelligence about its emerging rival, British India, this book explores China's altered understanding of its place in a global context.